Hybrid suburbia: New research perspectives in France and Southern California - Weber, Florian; Kühne, Olaf (Quaestiones Geographicae, 2017)
Geographical research on French and US suburbia has concentrated in recent decades on urban sprawl and concomitant processes of devaluation and exclusion. In the case of the French banlieues, with their much-publicised urban riots, this particular analytic focus has become overwhelming, with resultant loss to other developments and perspectives. However, certain districts in the first (or inner) ring of both French and US suburbia are currently showing distinct urbanisation tendencies in planning and architecture, evident in the new usage of brownfield sites and the ongoing demolition, replacement, and rededication of the older building core. Such processes induce population changes, e.g. the displacement of lower in favour of higher income groups. Overall, they result in an architectonic, social and cultural heterogeneity that escapes the specificity of received categories and merits the term hybridisation. The article describes and compares these processes as exemplified in Greater Paris and San Diego (Southern California).